Iso 9000 Acceptance And The Moderating Effect Of The Implementation Strategy: The Case Of The Faculty Of Business Management, Universiti Teknologi Mara, Shah Alam - Ismail , Noraini; Abdullah, Hazman Shah; Salamuddin, Norhana (Asian Academy of Management (AAM), 2006)
Academic institutions in the country are at present re-examining their business philosophy and trying to deliver quality education to remain attractive. Pressed by globalization, liberalization and accelerating competition, the education industry is facing up to these challenges by becoming more innovative in its transformation. Getting the ISO 9000 certification is quite a trendy phenomenon nowadays. But how do the academics react to this management system innovation? This paper tests a model of innovation acceptance (ISO 9000 certification) that conceptualizes interest, knowledge, involvement and perceived value as independent variables and implementation strategy as the moderator. One hundred and fifty structured questionnaires were distributed to the academic staff of the Faculty of Business Management where ISO initiatives were underway. The study shows that there is a significant correlation between perceived value with interest, knowledge, acceptance of innovation and implementation. Hierarchical multiple regression analysis indicates that the implementation strategy (participative strategy) enhances the relationship between interest and innovation acceptance. Interest can be cultivated, knowledge disseminated and involvement maximized through an implementation strategy that co-opts the staff from the inception of the change initiative.